The role of mindfulness in physical activity: a systematic review. (23rd November 2018) - Schneider, J.; Malinowski, P.; Watson, P. M.; Lattimore, P.
Summary: Despite continued public health campaigns to promote physical activity, a majority of the population is inactive. In recent years, mindfulness‐based approaches have been used in health and lifestyle interventions for physical activity promotion. We conducted a systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines to investigate the evidence for the potential of mindfulness‐based approaches for physical activity. We searched electronic databases for papers that met eligibility criteria and identified 40 studies for inclusion. Evidence from cross‐sectional studies ( n = 20) indicated a positive relationship between dispositional mindfulness and physical activity, particularly with psychological factors related to physical activity. Five studies found that the mindfulness–physical activity relationship was mediated by stress, psychological flexibility, negative affect and shame, satisfaction and state mindfulness. Evidence from mindfulness‐based interventions ( n = 20) suggested positive between‐subjects effects on physical activity, but interventions varied in duration, session length, group size, delivery, content and follow‐up. Mindfulness‐based interventions were more likely to be successful if they were physical activity‐specific and targeted psychological factors related to physical activity. The body of research shows a need for more methodologically rigorous studies to establish the effect of mindfulness on physical activity and to identify potential mechanisms involved in the mindfulness–physical activity relationship reliably.